Analisis Stimulus-Organism-Response dalam Komunikasi Persuasif Pendamping Program Pengembangan Karakter - Ukon Furkon Sukanda; Ajeng Pradesti; Riska Lula Devi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The involvement of orphaned beneficiaries in the character development program emphasizes the importance of a personal and persuasive approach to motivate active participation. This research uses the Stimulus-Organism-Response (S-O-R) theory to understand how persuasive message delivery influences the audience, focusing on the stimulus as a key element. With the right communication strategies, it is hoped that these beneficiaries will not only attend out of obligation but also because they understand the long-term benefits they will gain. A qualitative method with a case study approach is used to describe the importance of this program in developing the self-concept of the orphans. The research results show that the core finding, when linked to the S-O-R theory, is that the persuasive communication techniques used by the facilitators (stimulus) successfully motivated the orphans (organism) to participate more actively in the character development program, as seen in the increase in attendance and positive attitude changes (response). Communication barriers were also successfully overcome, enhancing the effectiveness of the techniques used. The techniques of association, integration, and itching device were effective in motivating the children, despite obstacles from both the facilitators and beneficiaries. Overall, the response to persuasive communication in 2024 showed improvement.